Winter Days in the Big Woods - Wilder, Laura Ingalls; Nang Chan Yeema (New York, USA HarperCollins Publishers, 1994)
A young pioneer girl and her family spend the winter in their log cabin in the Big Woods of Wisconsin.
Keywords: Story Collection